Representación Política Sustantiva En México: Una Mirada Desde La Subjetividad Política De Las Minorías Indígenas - Romero, Raúl Rocha; Hernández, Cintia Flores (European Scientific Journal, ESJ, 2017)
Within the framework of a larger study on the subjective, institutional and cultural factors that influence the substantive political representation of indigenous minorities in Mexico, the theoretical-methodological and empirical approach is presented in relation to the political subjectivity of indigenous peoples of the Mexican states of Oaxaca and Chiapas, with respect to the political representation of which they are subject by their federal deputies. A total of 46 interviews were conducted with Indians from Oaxaca and Chiapas in their respective places of residence. The results show a political subjectivity marked by descriptive, negative and valorative opinions. Indigenous people express not only the neglect they have been subjected to by representatives, but also the fact that national policy is totally alien to them. For the Indians of Mexico this means that they have not yet incorporated as citizens of the republic.